The problem with autocracy promotion. Issue 1 (2nd January 2016) - Tansey, Oisín
Abstract : Recent scholarship has increasingly focused on the international dimensions of authoritarian rule, and the idea of autocracy promotion has gained considerable academic currency. While the literature on autocracy promotion has identified some clear patterns of external support for autocratic incumbents, it has so far failed to demonstrate that these efforts can best be understood as a unified, coherent set of foreign policies that constitute intentional efforts to promote a particular regime type abroad. This article identifies the key deficiencies of existing treatments of the concept and identifies a roadmap to establish some conceptual clarity on the topic. It advances a "strict" definition of autocracy promotion that requires a clear intent on the part of an external actor to bolster autocracy as a form of political regime as well as an underlying motivation that rests in significant part on an ideological commitment to autocracy itself. It also introduces a new typology that places autocracy promotion within the wider context of the international politics of authoritarian rule.